Analisa Nilai Valuasi Startup Berdasarkan Faktor Keuangan Dan Faktor Non Keuangan Media Online PT. XYZ Bali - Putu Agustini, Ni Luh; Swastika, Putu Agus; Estiyanti, Ni Made (Politeknik Ganesha Medan, 2019)
Abstract The number of internet users in Indonesia has increased rapidly in the past two decades. Technological developments coincided with the growth of pioneering companies or startups, both failures or great successes. Fundraising is the lifeblood of startup, a steady stream of funds from various sources will greatly help the company.The success of startups, one of them can be seen from how much the value of the startup’s valuation, The greater the value then the opportunity to get investors' funds wide open. PT. XYZ is one of the startup of online media in Indonesia and the first in Bali, investment funds can certainly support and optimize the development of the company. Considering the importance of investment funds for the sustainability of the company, a valuation calculation is needed to gain an opportunity to receive funding. The important elements of the company, both in terms of financial and non-financial, will be the attraction of investors to invest. Keywords : Valuation, Startup, Investment